A new small karst-dwelling species of Cyrtodactylus (Reptilia: Squamata: Gekkonidae) from Java, Indonesia - Riyanto, Awal (Zootaxa, 2014)
A new small karst-dwelling species of the genus Cyrtodactylus is described from East Java and Special Province of Yogyakarta, Indonesia. Cyrtodactylus semiadii sp. nov. is a small species (SVL to 47.1 mm in females, 42.1 mm in males) distinguished from all other congeners by unique characters combination: short, robust, cylindrical tail, indistinct ventrolateral folds, absence of precloacal groove, absence of enlarged femoral scales, absence of precloacal and femoral pores and lack of enlarged median subcaudal scales. It is the third member of the genus recorded from Java.